DOP06 Deep characterization of IL-23 pathway in different gut segments and associated plasma biomarkers in inflammatory bowel disease. (30th January 2023) - Cairns, J; Monkley, S; Tian, S; Angermann, B; Liu, Z; Öberg, L; Muthas, D; Cabrera, C; Rapsomaniki, E; Fernández Llaneza, D; Olsson, M; Paraskos, J; et al.
Abstract: Background: The role of Interleukin 23 (IL-23) in the pathogenesis of both Crohn's disease (CD) and ulcerative colitis (UC) is well documented. However, more than half of patients do not respond or lose response to current anti-IL-23 treatments. Thus, we aimed to identify patients with IL-23-driven disease using gut segment-specific transcriptome analysis and quantification of IL-23 pathway cytokines in plasma to enable patient stratification in inflammatory bowel disease (IBD). Methods: Analyses of real-world data from the Study of a Prospective Adult Research Cohort with IBD (SPARC IBD) obtained from the IBD Plexus program of the Crohn's & Colitis Foundation including clinical, plasma biomarker (IL-22, IL-23, INF-γ, and IL-17A), and mucosal ileum and colon transcriptome data. Results: To differentiate IL-23 from TNF-driven disease, we performed gene set variation analysis (GSVA) using IL-23 and TNF gene sets and ileal and colonic transcriptome data from 1230 CD and 664 UC patients. An IL-23, but not TNF, transcriptional module was enriched in ileal compared to colonic biopsies in CD (p < 0.001). IL-23 pathway activity was significantly higher in uninflamed Ileal compared to colonic biopsies from CD patients (p < 0.001)). Importantly, IL-23 pathway activity was increased in intestinal biopsies from macroscopically inflamed compared to uninflamed regions, from all gut segments in both CD and UC and correlated with the endoscopic score for both diseases (Fig 1). We also observed higher plasma IL-22 levels in both CD and UC patients with moderate to severely active disease compared with patients in remission (Fig 2). We found that tissue IL-23 pathway activity was linked to plasma biomarker levels in general. The subgroup of CD patients with elevated plasma IL-22 levels showed higher IL-23 pathway activity in the ileum (p=0.003) and colon (p=0.013). In UC, patients with elevated plasma IL-22 levels showed higher IL-23 pathway activity in the sigmoid colon (p=0.001), but not the cecum (p=0.141) (Fig 3). Conclusion: IL-23 pathway activity in different segments of the gut may contribute differently to pathogenesis in CD, while IL-23 pathway activity is similar across colonic segments in UC. The association between plasma biomarker levels and gut tissue IL-23 pathway activity suggests that quantifying plasma IL-22 levels could be a valuable tool to assess the efficacy of anti-IL-23 therapy in IBD.